A Discrete Choice Experiment to Assess Cat Owners’ Preferences for Topical Antiparasitics and the Comparative Ease of Use of a Combined Selamectin and Sarolaner Formulation: An International Survey - Constantina N. Tsokana; George Valiakos; Kennedy Mwacalimba; Danielle Riley; Ashley Enstone; Robin Wyn; Tom Metcalf; Emily Melchior; Eleni Pavlidou; Andrea Wright (Animals, 2025)
Cat owners are involved in their cats’ healthcare, including the prevention of parasitic diseases. However, a comprehensive understanding of their preferences for feline antiparasitics is lacking. This study addresses this gap through a multifaceted methodology comprising three phases. In Phase 1, the physical properties and usability aspects of seven topical antiparasitic formulations were assessed. Within Phase 2, an ease-of-use study was conducted to evaluate the cat owners’ application experience with deidentified products representing three topical antiparasitics. Phase 3 included the identification and validation of product attributes most valued by pet owners through interviews with cat owners and veterinary experts. The product attributes identified informed the subsequent quantitative discrete choice experiment (DCE), which involved 1040 cat owners from different countries (Australia/New Zealand, Canada, Greece/Spain, and the UK) and aimed to analyze their preferences based on choices among product profiles mirroring four topical antiparasitics: selamectin–sarolaner, moxidectin–fluralaner, moxidectin–imidacloprid, and eprinomectin–esafoxolaner–praziquantel. Phase 1 showed that the selamectin–sarolaner formulation exhibits minimal odor, less stickiness, and less drying time. The ease-of-use study (Phase 2) showed that the blinded product representing the selamectin–sarolaner formulation was characterized by seamless application, rapid dispensing, and a sense of control during application. The quantitative DCE study (Phase 3) indicated a preference for the product profile mirroring the selamectin–sarolaner formulation among a global sample of cat owners. Demographic characteristics such as gender, age, and insurance status influenced their preferences. Key predictors for preferring the selamectin–sarolaner formulation over at least one comparator treatment included the ability to confirm successful administration, age restrictions, ease of application, and the time before the cat could sit on furniture following administration. These findings suggest that cat owners prioritize ease of use, safety, and overall user experience, providing valuable guidance for veterinary practitioners to make informed treatment recommendations.